Naturalistic prospective memory in older adults: Predictors of performance on a habitual task. Issue 5 (4th July 2017) - Cavuoto, Marina G.; Ong, Ben; Pike, Kerryn E.; Nicholas, Christian L.; Kinsella, Glynda J.
Abstract : Age-related difficulties in episodic prospective memory (PM) are common. However, little is known about habitual PM, which involves remembering to carry out intended actions that are regular and repeated. This is important for many health-related tasks and for maintaining independence in daily living activities. This study investigates, in older people, the predictors of habitual PM performance in a naturalistic setting. A group of 191 community-based, older adults (aged 65–89 years) wore an actigraph over two weeks. The habitual PM task involved pressing a button twice daily (Bed-time, Rise-time) on the actigraph. Accuracy of response was calculated for Bed-time and Rise-time, determined by light, movement, and diary data. The contribution of retrospective memory and executive function to PM performance was assessed. PM was more accurate at Bed-time compared to Rise-time ( p  < .01), and better in the first compared to the second week ( p  < .01). Retrospective memory contributed small but significant unique variance ( β  = .24) to PM accuracy. For older adults living in the community, both contextual factors (e.g., time of day) and retrospective memory are important for individuals' ability to remember to perform daily tasks. This is relevant when planning interventions for maintaining independent living in ageing.